Effect of Community-Based Health Insurance on Healthcare-Seeking Behavior for Childhood Illnesses Among Rural Mothers in Aneded District, East Gojjam Zone, Amhara Region, Northwest Ethiopia - Simieneh MM; Yitayal M; Gelagay AA (Dove Medical Press, 2021)
Muluye Molla Simieneh,1 Mezgebu Yitayal,2 Abebaw Addis Gelagay3 1Department of Public Health, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 2Department of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 3Department of Reproductive Health, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Mezgebu YitayalDepartment of Health Systems and Policy, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, P. O. Box 196, Gondar, EthiopiaTel +251 947 057683Email mezgebuy@gmail.comBackground: Community-based health insurance (CBHI) schemes have been implemented in developing countries to facilitate modern medical care access. However, studies conducted on the effect of CBHI on healthcare-seeking behavior (HSB) have been limited and revealed inconsistent results. Therefore, this study aimed to assess the effect of CBHI on mothers’ HSB for common under-five childhood illnesses.Methods: A community-based comparative cross-sectional study was conducted among 410 rural mothers (205 insured and 205 non-insured), and a multistage random sampling technique was used to select the study participants. Binary logistic regression and propensity score matching were used to identify factors associated with the mothers’ HSB, and estimate the effect of CBHI on mothers’ HSB, respectively.Results: The overall mother’s HSB for childhood illnesses was 48.8% (200/410). From those mothers who visited healthcare, 92.0% were married, 86.0% were unable to read and write, 94.5% were farmers, and 54.5% were from low wealth status, 58.50% had a family size of ≤ 5, 54.0% had children less than 24 months of age. Besides, 63.0% were members of CBHI, 37.0% perceived their child’s illness as severe, 78.0% made a shared decision to visit a health facility, and 67.5% lived within less than five Kms from the nearby health facilities. Being a member of CBHI, the child’s age, decision to visit a health facility, and perceived disease severity were predictors of HSB. The CBHI had a significant effect on the HSB for childhood illnesses with ATT of 28.7% (t = 3.959).Conclusion: The overall mothers’ HSB for common childhood illnesses was low though the CBHI has a significant effect. CBHI should be strengthened to improve the mothers’ HSB. It is also crucial to strengthen awareness creation regarding joint decision-making and educate mothers to visit the health facilities regardless of children’s age and disease severity.Keywords: effect, community-based health insurance, mothers, health-seeking behavior, childhood illnesses